Negotiating the Pandemic Cultural, National, and Individual Constructions of COVID-19 - Ali, Inayat; Davis-Floyd, Robbie (Routledge Studies in Health and Medical Anthropology, 2022)
This book centers on negotiations around cultural, governmental, and individual constructions of COVID-19. It considers how the coronavirus pandemic has been negotiated in different cultures and countries, with the final part of the volume focusing on South Asia and Pakistan in particular. The chapters include auto-ethnographic accounts and ethnographic explorations that reflect upon experiences of living with the pandemic and its implications for all areas of life. The book explicates people's dealings with COVID-19 at various levels, situates the spread of rumors, conspiracy theories, and new social rituals within micro- and/or macro-contexts, and describes the interplay between the virus and various institutionalized forms of inequalities and structural vulnerabilities. Bringing together a variety of perspectives, the volume relates to the past, describes the Covidian present, and offers futuristic implications. It enlists distinct imaginaries based on current understandings of an extraordinary challenge that holds significant importance for our human future.